A metastasis suppressor Pt-dendrimer nanozyme for the alleviation of glioblastoma. Issue 19 (6th May 2021) - An, Jong Min; Ju, Youngwon; Kim, Jeong Hee; Lee, Hyein; Jung, Yuna; Kim, Jaehoon; Kim, Yong Jun; Kim, Joohoon; Kim, Dokyoung
Abstract : The alleviation properties of a Pt-dendrimer nanozyme for GBM metastasis were introduced for the first time. The biological properties of the Pt-dendrimer nanozyme were demonstrated as a suppressor of GBM migration, invasion, and adhesion. Abstract : Nanozymes are nanostructure-based materials which mimic the enzymatic characteristics of natural enzymes. Biological applications of nanozymes have been highlighted in basic research, industry, and translational medicine as a new cutting-edge tool. In this work, and for the first time, we disclose a tumor alleviation property of a nanozyme that is made up of amine-terminated sixth-generation polyamidoamine dendrimers with encapsulated tiny platinum nanoparticles. We systematically conducted the synthesis and characterization of the dendrimer-encapsulated Pt nanoparticles (denoted Pt-dendrimer) and confirmed their enzymatic function (hydrogen peroxide (H2 O2 ) decomposition) within various cell lines (normal, cancerous), including glioblastoma (GBM) cells. By understanding the effects of the Pt-dendrimer at the gene level, especially related to cancer cell metastasis, we have thoroughly demonstrated its ability for tumor alleviation and suppressing GBM migration, invasion, and adhesion. The present findings show great promise for the application of the nanozyme for use in GBM-related basic research as well as at clinical sites.